(untitled) (International Journal of Engineering and Computer Science, 2014)
Voice telephony over mobile is currently supported at a cost using service provider such as GSM, or using IP service provider at cheaper cost. The purpose of this research is to design and implement a telephony program that uses WIFI in p2p (Peer -to- Peer) or WLAN (Wireless Local Area Network) as a means of communication between mobile phones at no cost. The system will allow users to search for other individuals within WIFI range and to establish free p2p voice connections, or to establish virtual connection through Access Points (AP), as well as giving the option to user to use GSM in the case of no WIFI connectivity is available. The system will use a novel algorithm to convert mobile number into IP address and use it as a mean for contacting other mobile over p2p or AP using WIFI technology. The software will use a correlation between current address books available in mobile phones to convert phone numbers into IP addresses. The system will allow user to make voice conversation, sending SMS (Short Message Service) as well as MMS. Inbox and outbox services, message delivery reports, and message drafts will be used for SMS and MMS management. The current system will only allow for one call per connection, and no call waiting, or conference calls.